2000
DOI: 10.1111/j.1728-4465.2000.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender Preference on Contraceptive Use and Fertility in Rural Egypt

Abstract: Data are used from two surveys of currently married women aged 15-44 conducted in 1979-80 and 1990-91 to explore the changing impact of gender preference on modern contraceptive use and on fertility in rural Menoufia, Egypt. The significantly positive effects on contraceptive use of having one or more sons in 1979 remained constant in 1990. Families without living sons had higher odds of having a birth than did families with two or more sons during 1979-80, and these relative odds were even higher in 1990-91 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
5
24
0
Order By: Relevance
“…This is consistent with Jordanian culture, a male-dominated culture, in which the wife relinquishes reproductive decisions to her husband (26,27). A husband's decision on choice of contraceptive method may be influenced by the number and sex of children; a Palestinian study found that husbands' desire was to have 2 sons, while in Jordan and Egypt the desire was for 3 sons (26,28,29). On the other hand, we found that husbands' desire for more children did not hold as a predictor for selecting contraceptive method after controlling for other factors.…”
Section: Discussionsupporting
confidence: 66%
“…This is consistent with Jordanian culture, a male-dominated culture, in which the wife relinquishes reproductive decisions to her husband (26,27). A husband's decision on choice of contraceptive method may be influenced by the number and sex of children; a Palestinian study found that husbands' desire was to have 2 sons, while in Jordan and Egypt the desire was for 3 sons (26,28,29). On the other hand, we found that husbands' desire for more children did not hold as a predictor for selecting contraceptive method after controlling for other factors.…”
Section: Discussionsupporting
confidence: 66%
“…As already shown in earlier studies (Yount et al, 2000), contraceptive use depends on the gender composition of earlier births.…”
Section: Mechanisms: Individual Choices or Social Norms?supporting
confidence: 65%
“…But other studies on India (Das Gupta, 1987 ;A. Basu, 1999 ;Rajan, Sudha, & Mohanachandran, 2000 ;Jayachandran, 2014), South Korea (Edlund & Lee, 2013), Egypt (Yount, Langsten, & Hill, 2000) or Sub-Saharan Africa (Klasen, 1996) have questioned this result. 11.…”
Section: Empirical Evidence So Farmentioning
confidence: 97%
“…This distortion declined over time so that the sex ratio at birth for most Muhafazas came within the confidence interval of the expected biological value in 1996. Son preference has been documented by Williamson (1976), Arnold (1992), United Nations (1998) and for rural Egypt by Yount, Langsten and Hill (2000). As births are not published at the subdivision level, we cannot estimate female birth underregistration at that level.…”
Section: Sources Of Data and Basic Proceduresmentioning
confidence: 93%